International finance : - Levi, Maurice D. (McGraw-Hill, 1996)
This text concentrates on the financial management practices, and current financial market environment of multinational corporations. A major revision of this best-seller, the third edition of the text has undergone a significant reorganization of material and updating. Furthermore, throughout this edition, many more illustrations and examples from popular business periodicals have been included to help connect real-world practice with aspects of modern theory.